2022
DOI: 10.1002/rse2.286
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring shallow coral reef exposure to environmental stressors using satellite earth observation: the reef environmental stress exposure toolbox (RESET)

Abstract: Coral reefs are significantly threatened by multiple environmental stressors associated with climate change. While there is growing recognition of the importance of interacting stressors on coral reefs, so far this has been primarily limited to in situ studies. Satellite remote sensing has potential for investigating coral reef exposure to multiple environmental stressors at a global scale over multiple years; however, current satellite monitoring is primarily focused on thermal stress. Here we collate nine en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 108 publications
(147 reference statements)
0
2
0
Order By: Relevance
“…The areas with higher coral stress index values were areas that were near large towns and cities with fishing pressure accounting for the majority of variation. Most recently, a Google Earth Engine based tool used a combination of stressors and reducers to find strong correlations between their stress exposure score and El Niño bleaching events for corals in the Red Sea, Chagos Archipelago, and Gilbert Islands (Williamson et al, 2022). While this tool extensively uses SST in their score along with other factors like wind, they do not include water clarity as the toolkit presented here.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The areas with higher coral stress index values were areas that were near large towns and cities with fishing pressure accounting for the majority of variation. Most recently, a Google Earth Engine based tool used a combination of stressors and reducers to find strong correlations between their stress exposure score and El Niño bleaching events for corals in the Red Sea, Chagos Archipelago, and Gilbert Islands (Williamson et al, 2022). While this tool extensively uses SST in their score along with other factors like wind, they do not include water clarity as the toolkit presented here.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, Degree Heating Weeks (DHW) is often used for assessing heat stress on coral. The NOAA Coral Reef Watch DHW product is widely used (Eakin et al, 2010;Baumann et al, 2019;De et al, 2021a;Johnson et al, 2022), but some studies have utilized Aqua MODIS SST to calculate DHW as well (Wouthuyzen et al, 2018;Williamson et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al monitored the mass coral bleaching effects using the thermal stress from sea surface temperature and high spatial-resolution Sentinel-2B remote sensing imagery systems [36]. Williamson et al developed a fuzzy logic-based Reef Environmental Stress Exposure Toolbox (RESET) for monitoring environmental stressors on shallow coral-reefs [37]. Meng et al designed a portable toolkit to monitor the health of coral-reefs and diagnose coral thermal stress using image processing software [38].…”
Section: Related Workmentioning
confidence: 99%
“…Satellite images have been implemented in operational marine monitoring programs of the water quality and habitat health in the GBR [40][41][42][43]. Several recent studies have demonstrated that methods using multiple datasets, including satellite imagery, are essential in the monitoring and management of remote, large and/or data-poor marine ecosystems such as those found in Oceania [44][45][46][47][48][49].…”
Section: Introductionmentioning
confidence: 99%